2012
DOI: 10.1002/adma.201200682
|View full text |Cite
|
Sign up to set email alerts
|

Grafted Crystalline Poly‐Perfluoroacrylate Structures for Superhydrophobic and Oleophobic Functional Coatings

Abstract: This report describes the preparation of superhydrophobic and oleophobic surfaces by grafting of poly(perfluorodecylacrylate) chains with initiated chemical vapor deposition on silicon substrates. The grafting enhances the formation of a semicrystalline phase. The crystalline structures reduce the polymer chain mobility, resulting in nonwetting surfaces with both water and mineral oil. On the contrary, the same contacting liquid easily wets the amorphous ungrafted polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 25 publications
4
76
0
Order By: Relevance
“…[36][37][38] While copolymerization helps by improving the mechanical properties of uoropoly-mers it negatively impacts the surface wettability of the lms due to a decrease in the uorine content. A bilayer strategy reported here for the rst time consists of a relatively thick, mechanically-robust, and highly-cross-linked network which is covered with an ultrathin uorine-rich layer producing coatings with both enhanced mechanical properties and low surface energy which is essential for icephobic applications.…”
mentioning
confidence: 99%
“…[36][37][38] While copolymerization helps by improving the mechanical properties of uoropoly-mers it negatively impacts the surface wettability of the lms due to a decrease in the uorine content. A bilayer strategy reported here for the rst time consists of a relatively thick, mechanically-robust, and highly-cross-linked network which is covered with an ultrathin uorine-rich layer producing coatings with both enhanced mechanical properties and low surface energy which is essential for icephobic applications.…”
mentioning
confidence: 99%
“…[11,13] The reactor was covered with a quartz top (2.5 cm thick) that allows real-time thickness monitoring by reflecting a 633 nm He-Ne laser source (JDS Uniphase) off the substrate/polymer and recording the interference signal intensity as a function of time. The reactor was pumped down by a mechanical Fomblin pump (Leybold, Trivac) and the pressure was monitored with a MKS capacitive gauge.…”
Section: Methodsmentioning
confidence: 99%
“…iCVD is a deposition technique that enables grafting of polymers to substrates and therefore promotes their adhesion to substrates to be durable against abrasion and erosion. [10][11][12] Unlike traditional polymer deposition techniques such as spin-coating, dipping, and ink-jet printing, iCVD provides ways to deposit graded polymers, copolymers which do not have common solvents, and multilayered polymers which are covalently bonded at their interface. [13,14] The conformal nature of the iCVD technique also enables the integration of polymer thin films onto engineering surfaces that have roughened features or nanostructured topography.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the interaction between the polymer and its surroundings -either the substrate or the external environment -perpendicular to the surface modifying the wettability and roughness of the fi lm. A second study [ 26 ] revealed that grafting of PFDA polymer chains enhances the crystalline order of the coating, resulting in fi ber-like structures. The grafted fi lms exhibit superhydrophobic and oleophobic properties.…”
Section: Tailored Surfaces and Interfacesmentioning
confidence: 99%
“…Adapted with permission. [ 26 ] Copyright 2012, Wiley-VCH. b) 3D pattern obtained via buckling of iCVD pEGDA fi lms grafted to a PDMS substrate.…”
Section: Tailored Surfaces and Interfacesmentioning
confidence: 99%